Exposure to ozone induces a systemic inflammatory response: possible source of the neurological alterations induced by this gas. (1st July 2014) - González-Guevara, Edith; Martínez-Lazcano, Juan Carlos; Custodio, Verónica; Hernández-Cerón, Miguel; Rubio, Carmen; Paz, Carlos
Abstract: The World Health Organization identified urban outdoor air pollution as the eighth highest mortality risk factor in high-income countries. Exposure to ambient pollutants such as ozone (O3 ) increases the number of hospital admissions. O3 is a highly reactive gas that reacts with cells lining the airways, producing the formation of reactive oxygen species and inflammation. Beyond the respiratory system, O3 exposure also produces fatigue, lethargy, headaches, and significant decrease in rapid-eye-movement sleep related to an increase in slow-wave sleep. Interestingly, these sleep changes can be significantly mitigated by treatment with indomethacin, which suggests that an inflammatory mechanism may be responsible for these neurological symptoms. To characterize the inflammatory mechanisms by which O3 affects tissues outside the pulmonary system, we evaluated inflammatory factors in both lung and brain. Rats exposed to 1 part per million O3 for 1, 3 or 6 h, as well as rats exposed daily for 1 or 3 h over five consecutive days, showed increases in TNF-α and IL-6 levels within the lungs as well as increases in TNF-α, IL-6, NF-κB p50 and GFAP levels in the cerebral cortex. These results support the hypothesis that the neuroinflammatory response may be responsible for the central nervous system effects of O3 exposure.